The Legacy of Painting Values, Techniques, and Aesthetics through Art Education: A Case Study of Cirebon Glass Painting in the Contemporary Era - Falah, Asep Mifatahul; Ramli, Zaenudin; Cahyana, Agus (Lembaga Riset Mutiara Akbar, 2025)
Cirebon glass painting is one of the traditional art forms that contains cultural values, distinctive techniques, and local aesthetics. In facing the challenges of modern times, the sustainability of Cirebon glass painting demands a contextual and adaptive inheritance strategy. This study aims to examine how the values, techniques, and aesthetics in the tradition of Cirebon glass painting are passed down through art education, both in the formal (schools and art colleges) and non-formal (studios and communities) realms. Using a qualitative method with an ethnographic case study approach, data was collected through observation, interviews, and visual documentation. The results show that the inheritance of glass painting does not solely depend on technical skills, but also on the internalization of cultural values and understanding of local aesthetics. Art education plays a role as a medium for intergenerational inheritance, although in its implementation it faces various challenges, such as limited curriculum integration, lack of regeneration of artists, and the need for innovative learning methods that are in accordance with the contemporary cultural context. This study recommends strengthening collaboration between educational institutions, traditional art practitioners and communities in designing a sustainable art inheritance model.